Factors Influencing the Acceptance of Transrectal Ultrasound-Guided Prostate Biopsies - Hwang, Ji Won; Bang, Woo Jin; Oh, Cheol Young; Yoo, Changhee; Cho, Jin Seon (Korean journal of urology, 2014)
This study aimed to improve prostate biopsy compliance by analyzing the factors that influence the acceptance of prostate biopsy by patients to whom transrectal ultrasound (TRUS)-guided prostate biopsy is recommended for suspected prostate cancer. The subjects of this study were 268 patients to whom TRUS-guided prostate biopsy was recommended from January to June 2011 and who completed a questionnaire. Patients who showed a prostate-specific antigen (PSA) increase to more than 4.0 ng/mL or abnormal findings on a digital rectal examination and TRUS were recommended to undergo prostate biopsy. The questionnaire consisted of 9 questions about the subjects' demographic characteristics and 15 questions that assessed their knowledge of prostate disease. Fisher exact probability test was conducted to assess the influence of the demographic characteristics and levels of knowledge of prostate disease on acceptance of prostate biopsy. The mean age of the subjects was 66.2 years (range, 43-83 years). Of the cohort, 188 patients (70.7%) agreed to the prostate biopsy and 78 patients (29.3%) refused. In terms of demographic characteristics, the patients' acceptance of prostate biopsy was associated only with education level. Patients with relatively lower education levels had a higher acceptance rate for prostate biopsy (80.0% vs. 65.9%, p=0.018). Other demographic factors, as well as the degree of knowledge of prostate disease, had no significant effect on the acceptance rate. The patients' acceptance of prostate biopsy can be influenced by demographic characteristics, especially education level. Therefore, when prostate biopsy is recommended to patients, their demographic characteristics should be taken into consideration.